Effect of the Addition of Polysaccharide Hydrocolloids on Sensory Quality, Color Parameters, and Anthocyanin Stabilization in Cloudy Strawberry Beverages - Mirosława Teleszko; Paulina Nowicka; Aneta Wojdyło (Polish Journal of Food and Nutrition Sciences)
This manuscript presents results of the qualitative characteristics of strawberry cloudy juice and beverages with the addition of 0.2% and 0.3% of carboxymethylcellulose (CMC), guar gum (GG), locust bean gum (LBG), and xanthan gum (XG). Fresh products were evaluated with reference to their sensory quality (5-point scale). Changes in L*a*b* parameters and in the stability of anthocyanins (ultra-performance liquid chromatography–mass spectrometry) were monitored in the storage experiment (6 months, 4°C). Most of the hydrocolloids have contributed to the improvement of the taste and the consistency of strawberry products. In overall taste evaluation, the highest scores were given to the samples with CMC, whereas in the consistency evaluation, to the samples with CMC, GG, and LBG addition at a dose of 0.2%. The study of color parameters of the products has indicated significant changes in their chromatic space during storage. After 6 months, beverages with CMC, GG, and LBG were darker in comparison to the control sample. The contribution of red color in beverages was higher, and of yellow color was lower than in the strawberry juice. Strawberry juice was characterized by a high degree of anthocyanins degradation ( Dd =84%), especially of pelargonidin-3-glucoside and cyanidin-3-malonylglucoside. The use of hydrocolloids has contributed to the partial reduction of this phenomenon. In conclusion, the most beneficial protective effect on anthocyanins ( Dd = 65%) and the impact on the sensory characteristics in strawberry beverages was provided by LBG application.